Inter-Relationship of Circulating Biochemical Markers of Oxidative Stress and Thyroid Hormones in newly Diagnosed Schizophrenics: Perspective study from Local Population of Punjab Pakistan (Medical Forum Monthly, 2024)
Objective: Current study was conducted to determine the fluctuations of various circulating biomarkers including thyroid hormones, hepatic enzymes, oxidative stress markers as well as electrolytes in schizophrenics.Study Design. Cross Sectional Study.Place and Duration of Study: This study was conducted at Psychiatric Clinic of Jinnah Hospital, Mental Hospital from Jan. 2013 to Oct. 2013.Materials and Methods: Seventy five acute schizophrenics and twenty five healthy individuals were selected for this study. Patients with chronic infections, diabetic history, liver disease or any other history of drugs including smoking and/or drinking alcohol were excluded from the study.Results: Elevated levels of oxidative stress in the form of malondialdehyde (MDA) (7.8±2.71*) were observed in schizophrenics. Similarly raised levels of T3 (6.9±1.31*) and T4 (61.2±15.44*) were found in patients as compared to control. Electrolytes like Na, K, Ca and Mg showed alterations in the serum of both patients and control.Conclusion: All the circulating biochemical markers were statistically significant (P<0.05). It is concluded that lipid peroxidation may has association with thyroid hormones and electrolytes. Moreover, alleviated concentration of anti-oxidant biomarkers like SOD, catalase and GSH may play a central role in schizophrenics and anti-oxidant therapy may be useful for the management of this psychiatric disorder.